Optimal tuning and assessment of inertial dampers with grounded inerter for vibration control of seismically excited base-isolated systems. (1st October 2019) - De Angelis, Maurizio; Giaralis, Agathoklis; Petrini, Francesco; Pietrosanti, Daniele
Highlights: Energy-based optimal design and performance evaluation of TMDI-equipped BIS. Quantification of seismic energy dissipation trade-off between BIS and TMDI. Optimal TMDI design charts on the inertial plane for performance-based BIS design. Assessment of colored frequency content excitation on the performance of TMDI. Wavelet-based interpretation performance assessment of TMDI subject to GMs. Abstract: In this paper, the concept of an ideal grounded linear inerter, endowing supplemental inertia to passive linear tuned mass-dampers (TMDs) through its inertance property without increasing the TMD mass, is considered to reduce lateral displacement demands in base isolated structural systems (BISs). Optimal tuned mass-damper-inerter (TMDI) design parameters are numerically determined to maximize energy dissipation by the TMDI under stationary white noise support excitation. Performance of these optimally designed TMDI-equipped BISs is assessed for stationary white and colored noise excitations as well as for four recorded earthquake acceleration ground motions (GMs) with different non-stationary frequency content. It is found that for fixed mass ratio the inclusion of the grounded inerter reduces significantly secondary mass displacement and stroke for all considered excitations while it improves appreciably BIS displacement demands except for the particular case of a near-fault accelerogram characterized by early arrival of a high-energy low-frequency pulse as captured in its wavelet spectrogram. More importantly, it leads further to reductions to BIS acceleration demands with the exception of colored noise excitation for which an insignificant increase is noted. The positive effects of the inerter saturate with increasing inertance and BIS damping ratio demonstrating that small inertance values are more effective in vibration suppression of BISs with low inherent damping. Overall, it is recommended to combine low damping isolation layers with large inertance and low secondary mass TMDIs.